2020
DOI: 10.14309/ajg.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab for Perianal Crohn's Disease: The BioLAP Multicenter Study From the GETAID

Abstract: INTRODUCTION: New therapeutic options for patients with Crohn's disease (CD) with perianal lesions failing anti–tumor necrosis factor (TNF) agents are needed. We aimed to assess the effectiveness of ustekinumab in perianal CD (pCD) and predictors of clinical success in a real-life multicenter cohort. METHODS: We conducted a national multicenter retrospective cohort study in patients with either active or inactive pCD who received ustekinumab. In patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 30 publications
2
38
1
2
Order By: Relevance
“…We did not find any difference between the two treatments on the rate of healing of perianal lesions, although recent data suggested more promising results for ustekinumab in patients with perianal lesions 28 than for vedolizumab 29 . In addition, both drugs were very safe in our cohort with no difference between the two drugs as previously widely reported 8‐10 …”
Section: Discussionsupporting
confidence: 51%
“…We did not find any difference between the two treatments on the rate of healing of perianal lesions, although recent data suggested more promising results for ustekinumab in patients with perianal lesions 28 than for vedolizumab 29 . In addition, both drugs were very safe in our cohort with no difference between the two drugs as previously widely reported 8‐10 …”
Section: Discussionsupporting
confidence: 51%
“…In this cohort, no predictive factors were associated with the main outcomes, and only the number of prior anti-TNF agents (≥3 drugs) showed a trend toward a reduced response rate. No additional predictive factors have been associated with fistula response or healing in real-world experience reported so far (23,24,38,64,65).…”
Section: Disease-related Factorsmentioning
confidence: 85%
“…Data from uncontrolled real-world studies have reported heterogeneous results on fistula response and closure rates (23,24,64,65). In 148 patients with active perianal disease included in a observational cohort from the GETAID, 39% achieved treatment success with UST (64). In this cohort, no predictive factors were associated with the main outcomes, and only the number of prior anti-TNF agents (≥3 drugs) showed a trend toward a reduced response rate.…”
Section: Disease-related Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Existing first‐line therapies (mainly, tumour necrosis factor [TNF] antagonists) are only moderately effective in achieving long‐term fistula healing, even when used optimally 1,2 . Furthermore, the second generation biologic agents vedolizumab and ustekinumab appear to have only marginal benefit when used as salvage therapies 3,4 . Although promising, mesenchymal stem cell therapy is not yet widely available 5 .…”
mentioning
confidence: 99%